An Improved Deadbeat Predictive Stator Flux Control With Reduced-Order Disturbance Observer for In-Wheel PMSMs - Sun, Xiaodong; Zhang, Yao; Lei, Gang; Guo, Youguang; Zhu, Jianguo (IEEE/ASME transactions on mechatronics, 2022)
In this article, an improved deadbeat predictive stator flux control (DPSFC) based on disturbance observer is proposed to address the problems of the steady-state tracking error and robustness decrease due to the detrimental parameter mismatch and disturbance. First, the sensitivity of conventional deadbeat predictive current control to the parameter variation, including flux linkage, stator inductance, and resistance, is analyzed. Then, a reduced-order observer based on additional disturbance state variables in discrete time is designed to predict the future stator flux and observe the system disturbance caused by parameter mismatch. The proposed DPSFC method is able to enhance the robustness of the drive performance effectively via applying the estimated disturbance as the feed-forward compensations of one-step delay and stator voltage. Additionally, the theoretical proof is given. Finally, the superiority of the proposed control method is validated by simulations and experiments on a prototype of an in-wheel permanent magnet synchronous motor drive.